2015
DOI: 10.5966/sctm.2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Human Umbilical Mesenchymal Stem Cells From Wharton's Jelly in the Treatment of Rat Peritoneal Dialysis-Induced Fibrosis

Abstract: Peritoneal fibrosis is a complication of continuous, ambulatory peritoneal dialysis in patients with end‐stage renal disease who are undergoing long‐term peritoneal dialysis. Intraperitoneal injection of human umbilical mesenchymal stem cells (HUMSCs) in rats ameliorated peritoneal dialysis/methylglyoxal‐induced abdominal cocoon formation, peritoneal fibrosis, inflammation, neoangiogenesis, and ultrafiltration failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 74 publications
(78 reference statements)
1
33
0
Order By: Relevance
“…Increasing evidences showed that HUMSCs exhibited long-term survival within different organs in rats and, therefore, could serve as an excellent cell source suitable for xenograft [39][40][41][42][43][44][45][46][47]. Experimental owchart for inducing PF in rats' left lung, administration of therapeutic agents nintedanib and pirfenidone, and transplantation of HUMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences showed that HUMSCs exhibited long-term survival within different organs in rats and, therefore, could serve as an excellent cell source suitable for xenograft [39][40][41][42][43][44][45][46][47]. Experimental owchart for inducing PF in rats' left lung, administration of therapeutic agents nintedanib and pirfenidone, and transplantation of HUMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the number of transplanted stem cells is considered as an important issue to regeneration, HUMSCs were implanted into different target-organs depending on the diseases [40][41][42][43][44][45][46][47][48]. In this study HUMSCs were implanted intratracheally to allow most transplanted stem cells migrating into damaged lung.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several experimental studies have already demonstrated that intraperitoneally injection of MSCs is able to attenuate peritoneal inflammation and fibrosis in rodent models of peritoneal dialysis [4244], indicating the possibility of using PD effluent-derived MSCs to reduce peritoneal membrane injury and fibrosis in PD patients.…”
Section: Discussionmentioning
confidence: 99%